PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - ANDRES PARU NUBATONIS; JOAN YULIANA HUTAPEA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This study was conducted to determine the effect of working environment on employee performances in Petrosea Offshore Supply Base - Sorong. The methodology of this research is quantitative research that use questionnaire for instruments to got data. The mode of sampling techniques, we are using an non-probability mode of sampling model, and the population in this research are the all employees on Petrosea Offshore Supply Base - Sorong, with about 68 persons. Which were taken on a certain time or period of timeline. The analysis model used is a descriptive of statistical analysis system, coefficient of determination test, t significant test. The results of this study showed that there werw a positive and very significant effect reality between an environment and the employee performances. Work Environment got a beta coefficient value of 0.442 which means the Work of Environment actually has a positive and also significant effect mode on the Employee’s Performance within a value of number such as 0.000